Molecular Irregularity Indices of Nanostar, Fullerene, and Polymer Dendrimers - Xie Qing; Zhen Wang; Mobeen Munir; Haseeb Ahmad (Journal of Chemistry)
Dendrimers are highly branched organic macromolecules with successive layers of branch units surrounding a central core. Some properties like toxicity, entropy, and heats of vaporization of these dendrimers can be forecasted using topological indices. The present article is devoted to study of irregularity indices of three well-known classes of dendrimers, namely, nanostar dendrimer D[p], fullerene dendrimer NS4[p], and polymer dendrimerNS5[p], where p is the step size. We also see the relation of irregularity of these dendrimers on the step size graphically.